Expansion Strategy in Translating English Subtitle of A Series “The Recruit” Season 2 Episode 1 Into Indonesian - Sunarti Desrieny Tambunan (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Translation is the process of transferring or transposing a message or knowledge from texts or utterances from at least two different languages. This present research specifically discusses the work of Audiovisual Translation (AVT), subtitling. This present research will find out the English subtitle that is translated into Indonesian using expansion strategy from a series entitled “The Recruit” Season 2 Episode 1. The theory about expansion strategy is based on Gottlieb (1992). A descriptive qualitative research is applied in this present research. The result reveals that 11 data of English subtitle are translated into Indonesian using expansion or addition strategy.